A journey from a corruption port to a tax haven - Shafik Hebous; Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2011)
We sketch a model according to which tax havens attract corporate income generated in corrupted countries. In our framework, tax havens have two opposite effects on welfare. First, tax havens' services have a positive effect on welfare through encouraging investment by firms fearing expropriation and bribes in corrupt countries. Second, by supporting corruption and the concealment of officials' bribes, tax havens discourage the provision of public goods and hence have also a negative effect on welfare. The net welfare effect depends on the specified preferences and parameters. One source of this ambiguity is that the presence of multinational firms in corrupted countries is positively associated with demanding tax havens' operations. Using firm-level data, we provide empirical support for this hypothesis.
Keywords: F23; H25; H32; 330; tax havens; tax avoidance; tax evasion; multinational firms; corruption